Dampak berita makroekonomi terhadap fluktuasi nilai tukar di Indonesia - Badara Shofi Dana; Moh. Adenan; Zainuri Zainuri (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2019)
The short-term exchange rate fluctuations can be explained by the microstructure approach of the foreign exchange market. The concept argues that macroeconomic news (news in the newspaper) can affect the exchange rate in the foreign exchange market by changing market actors’ assumptions . This study seeks to analyze the impacts of domestic and Chinese macroeconomic news on exchange rate fluctuation in Indonesia. The study uses exchange rates and domestic and Chinese macroeconomic news from2/1/ 2013 to 31/12/2018. Macroeconomic news consist of economic growth (GDP), retail sales and current account. By using the Generalized Methods of Moments (GMM) as the analysis tool, the study indicate that domestic and Chinese macroeconomic news affect exchange rate movements in Indonesia. Thus, this study suggests that Indonesia needs to maintain its macroeconomic fundamentals to mitigate the impacts of macroeconomic news. Further, increasing the efficiency and credibility of financial markets is crucial to stabilize exchange rate movements.